Analysis of SWOT Strategy in Sustainable Management of Mangrove Ecosystems in Kaliwlingi Village, Brebes Sub-district, Brebes District - Mohamad Qomar Syarifudin; Budi Rianto; Nuhman Nuhman (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
This study aims to obtain a strategy for managing sustainable mangrove ecosystems in Kaliwlingi Village, Brebes Sub-district, Brebes District. This study uses qualitative research with phenomenological methods. The data needed in this research is primary data obtained directly from respondents and secondary data obtained from data sources that do not directly provide data. The analytical method used in this research is the analysis of Strengths, Weaknesses, Opportunities and Threats (SWOT), and Quantitative Strategic Planning Matrix (QSPM) to determine the right strategy in managing sustainable mangrove ecosystems. The results of the Internal Factor Evaluation (IFE) calculation have a score of 2.21, which is below the average score of 2.50, indicating a less strong internal position. The results of the External Factor Evaluation (EFE) calculation show that the total score of 2.03 is below the average score of 2.50, indicating a less strong external position. The integration stage of IFE and EFE uses a SWOT matrix. The results of the combined score between IFE and EFE are 2.21; 2.03 in the first quadrant position, which is a favorable situation. The results of the QSPM show the Total Attractiveness Score (TAS) of strategy I as much as 6,009 has the highest TAS value and is the chosen alternative priority strategy. The results of the study show that the expansion strategy that must be taken by the Brebes Regency Government is to provide opportunities for the community to manage the mangrove ecosystem independently with assistance from the Government of Brebes District.